Mechanism and application of surface-initiated ATRP in the presence of a Zn0 plate. Issue 44 (4th November 2020) - Faggion Albers, Rebecca; Yan, Wenqing; Romio, Matteo; Leite, Edson R.; Spencer, Nicholas D.; Matyjaszewski, Krzysztof; Benetti, Edmondo M.
Abstract : SI-Zn 0 -ATRP enables the synthesis of chemically different polymer brushes under full ambient conditions, using just microliter volumes of reaction solutions. Abstract : Surface-initiated atom transfer radical polymerization in the presence of a Zn 0 plate (SI-Zn 0 -ATRP) enables the rapid synthesis of chemically diverse polymer brushes from both planar inorganic supports, and fabrics made of natural fibers. This process enables the controlled formation of polymer-brush layers on a variety of substrates, without the need for either inert conditions or lengthy deoxygenation procedures of the reaction mixtures.